Genotoxic effect of zinc and cadmium following single and binary mixture exposures in tilapia (Oreochromis niloticus) using micronucleus test - Abu Bakar, S.N.N.; Ashriya, A.; Shuib, A.S.; Razak, S.A. (Universiti Kebangsaan Malaysia, 2014)
The aim of this study was to investigate the genotoxicity effect of Cd and Zn and their binary mixtures in tilapia fish Oreochromis niloticus using the micronucleus test. Two cytogenetic end points were considered; the frequencies of micronucleated cells and nuclear abnormalities. Fishes were exposed to 4.63 mg/L Cd, 7.50 mg/L Zn and 4.63 mg/L Cd + 7.50 mg/L Zn mixture for the period of 24, 48, 72 and 96 h. The results showed that the frequencies of micronuclei and nuclear abnormalities in the erythrocyte were significantly increased in all groups of treatments when compared with the control group (0 exposures). In addition, the highest frequencies of micronucleated and nuclear abnormalities were obtained after 48 h exposure in almost all cases (except in the mixture of Cd+Zn) and decreased after 72 and 96 h exposure. Frequencies of micronuclei and erythrocytes with nuclear abnormalities exposed to a mixture of Cd+Zn in O. niloticus were always lower at all-time points (after 24, 48, 72 and 96 h) than that of a single Cd and Zn exposure. Therefore, the study demonstrated that the genotoxic potential of these metal compounds and the simultaneous treatment of Cd and Zn suggest the presence of antagonistic interactions.